2015
DOI: 10.1021/id500028m
|View full text |Cite
|
Sign up to set email alerts
|

Host-Mediated Bioactivation of Pyrazinamide: Implications for Efficacy, Resistance, and Therapeutic Alternatives

Abstract: Pyrazinamide has played a critical role in shortening therapy against drug-sensitive, drug-resistant, active, and latent tuberculosis (TB). Despite widespread recognition of its therapeutic importance, the sterilizing properties of this 60-year-old drug remain an enigma given its rather poor activity in vitro. Here we revisit longstanding paradigms and offer pharmacokinetic explanations for the apparent disconnect between in vitro activity and clinical impact. We show substantial host-mediated conversion of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 60 publications
(127 reference statements)
5
112
0
Order By: Relevance
“…The large changes in pK a predicted for benzimidazoles with sulfide/sulfoxide substituents, as well as the observation of uncoupling activity for the sulfides, are consistent with earlier work on sulfoxide/sulfide proton pump inhibitors (89), where uncoupling was observed with the sulfides, and suggests possible routes to new (pro)drug leads with multitarget (enzyme and uncoupler) activity. This prodrug activity involving the host is also a contributor to the activity of a standard TB drug, pyrazinamide, which is now thought to act, in large part, as pyrazinoic acid, a modest uncoupler that has multiple targets (39,90). A pictorial summary of a selection of such enzyme/uncoupler multitarget inhibitors is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large changes in pK a predicted for benzimidazoles with sulfide/sulfoxide substituents, as well as the observation of uncoupling activity for the sulfides, are consistent with earlier work on sulfoxide/sulfide proton pump inhibitors (89), where uncoupling was observed with the sulfides, and suggests possible routes to new (pro)drug leads with multitarget (enzyme and uncoupler) activity. This prodrug activity involving the host is also a contributor to the activity of a standard TB drug, pyrazinamide, which is now thought to act, in large part, as pyrazinoic acid, a modest uncoupler that has multiple targets (39,90). A pictorial summary of a selection of such enzyme/uncoupler multitarget inhibitors is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Niclosamide (12) and tizoxanide (14) are both FDA-approved, and closantel (15) is an anthelmintic uncoupler in veterinary use, and all could provide leads for new and improved inhibitors that target other pathogens. There has also been considerable renewed interest (39) in the use of pyrazinoic acid (16), which functions, at least in part, as a protonophore uncoupler, for treating TB (39,40), stimulating our interest in discovering new TB drug leads with uncoupler activity.…”
mentioning
confidence: 99%
“…If FadD2 inhibition in vivo does indeed confer PZA hypersusceptibility, lower doses of PZA could be administered, in turn reducing adverse drug reactions, expediting the sterilization of infection, and mitigating the proliferation of drug-resistant bacilli. Since lower doses of PZA would presumably be required for activity, it is possible that the coadministration of a FadD2 inhibitor with a normal dose of PZA could overcome the resistance resulting from the pncA loss of function by relying on host amidase activity for PZA bioactivation (33). Further, the potentiation of susceptibility could subvert pncA-linked resistance by enabling the efficacious use of POA in lieu of PZA.…”
Section: ) (B) Intracellularmentioning
confidence: 99%
“…Recent data indicate that POA is, in fact, orally bioavailable. The same study showed that host-mediated conversion of PZA to POA occurs and that POA easily diffuses in tissues (9), reviving interest in POA as a therapeutic solution for MDR-TB patients.…”
mentioning
confidence: 91%
“…The MIC of POA against M. tuberculosis is 16 to 32 g/ml in 7H10 media at pH 5.8 (8) and between 62 and 496 g/ml at pH 6.5 in 7H9 or 7H11, which may be up to 4-fold lower than the PZA MIC (9). Past studies suggested that POA was not orally bioavailable or was rapidly metabolized to inactive products (10).…”
mentioning
confidence: 99%